2015
DOI: 10.7554/elife.08627
|View full text |Cite
|
Sign up to set email alerts
|

The 133-kDa N-terminal domain enables myosin 15 to maintain mechanotransducing stereocilia and is essential for hearing

Abstract: The precise assembly of inner ear hair cell stereocilia into rows of increasing height is critical for mechanotransduction and the sense of hearing. Yet, how the lengths of actin-based stereocilia are regulated remains poorly understood. Mutations of the molecular motor myosin 15 stunt stereocilia growth and cause deafness. We found that hair cells express two isoforms of myosin 15 that differ by inclusion of an 133-kDa N-terminal domain, and that these isoforms can selectively traffic to different stereocilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(129 citation statements)
references
References 61 publications
5
122
1
Order By: Relevance
“…The failure of Whrn , Gpsm2 and Gnai3 cKOs stereocilia to elongate despite the localization of myosin 15, suggests that these proteins assemble in a macromolecular complex (including Eps8) to regulate actin polymerization at the stereocilia tips. Interestingly, it was recently shown that the distribution of whirlin on the tallest row of stereocilia was dependent upon the isoform 2 of myosin 15 (short form)38. It is therefore probable that Gpsm2 and Gα i3 are part of a preferential complex with myosin 15 isoform 2 and whirlin.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of Whrn , Gpsm2 and Gnai3 cKOs stereocilia to elongate despite the localization of myosin 15, suggests that these proteins assemble in a macromolecular complex (including Eps8) to regulate actin polymerization at the stereocilia tips. Interestingly, it was recently shown that the distribution of whirlin on the tallest row of stereocilia was dependent upon the isoform 2 of myosin 15 (short form)38. It is therefore probable that Gpsm2 and Gα i3 are part of a preferential complex with myosin 15 isoform 2 and whirlin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the protein composition of stereocilia tips differs in the tallest row of the bundle compared to those in shorter rows. In particular, EPS8 is enriched in row 1 while EPS8L2 and TWF2 are largely restricted to rows 2 and 3 along with the long splice isoform of myosin XVa [2,24,26,27]. This localization pattern is likely important for generating or maintaining the staircase morphology of the bundle.…”
Section: Morphological and Molecular Structure Of Stereocilia Bundlesmentioning
confidence: 99%
“…4C). The morphology of the mechanotransducing stereocilia is also particularly sensitive to perturbation of the actin cytoskeleton as loss or mutation of several cytoskeletal proteins, including the long isoform of myosin XVa, fascin-2, β-actin, Esp8L2, actin interacting protein 1 (AIP1) and ADF result in shortening of these stereocilia while not impacting the length of the non-mechanotransducing row [2,4,5,69,27]. …”
Section: Stereocilia Actin Dynamics: the Tip Turnover Modelmentioning
confidence: 99%
“…More recently, two Myo15a isoforms have been identified to serve differential roles in hair bundle morphology [93 •• ]. Isoform 1 contains a long N-terminal extension and targets to the tips of the shorter stereocilia rows [93 •• ].…”
Section: Myth4-ferm Myosin Cargoes and Physiological Functionsmentioning
confidence: 99%
“…More recently, two Myo15a isoforms have been identified to serve differential roles in hair bundle morphology [93 •• ]. Isoform 1 contains a long N-terminal extension and targets to the tips of the shorter stereocilia rows [93 •• ]. Conversely, the isoform lacking this extension, isoform 2, localizes to the longest stereocilia row and is sufficient to target the cargo proteins Eps8 and whirlin [93 •• ].…”
Section: Myth4-ferm Myosin Cargoes and Physiological Functionsmentioning
confidence: 99%